The Role of Metal-Organic Frameworks in Moderating Platinum-Based Ethanol Electrooxidation Catalysts - Fritzke, Jana B.; Essbach, Claudia; Wollmann, Philipp; Khan, Arafat H.; Senkovska, Irena; Weidinger, Inez M.; Kaskel, Stefan; Brunner, Eike (Journal of Physical Chemistry C, 2021)
Alcohol electrooxidation is an important reaction, for example, for fuel-cell applications or production of fine chemicals and pharmaceuticals. However, the reaction pathways of this reaction are not yet fully understood and optimized catalysts are necessary. Metal-organic frameworks can moderate such catalysts by forming a thin membrane acting as a filter to access the active center. Here, we present a study combiningin situandex situNMR spectroscopy within situRaman spectroscopy in order to investigate the influence of MOF coatings under voltage variation on the rate and selectivity of ethanol electrooxidation. The commercial Pt-catalyst Vulcan XC 72R/Pt is compared with a ZIF-8-functionalized Pt-catalyst (ZIF: zeolitic imidazolate framework). The appliedin situtechniques provide complementary information. Raman spectroscopic detection focuses on the surface of the working electrode. Several adsorption processes taking place on the catalyst surface are monitored. The ZIF-8-functionalization of the catalyst leads to an increased amount of adsorbed species on the electrode surface. In contrast, thein situNMR technique detects all dissolved and sufficiently mobile13C-bearing species in the detection coil region containing the electrochemical cell. The applied voltages allow investigating the influence of water activation on the Pt catalyst upon the alcohol oxidation reaction. ZIF-8-functionalization of the Pt-based catalyst mainly affects the product distribution. As demonstrated byex situ13C solid-state NMR spectroscopy, ethanol is adsorbed and partially immobilized by ZIF-8. Ethanol oxidation directly at the Pt-containing catalyst is observed in NMR experiments even without an applied voltage at low loadings.
CRIS-Team Scopus Importer:2022-04-14